PENGARUH PEMBIAYAAN JUAL BELI, PEMBIAYAAN BAGI HASIL, NON PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO, CAPITAL ADEQUACY RATIO, BEBAN OPERASIONAL PENDAPATAN OPERASIONAL TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2012-2016 - Seli Novitasari, 13.05.52.0220; Aini, Nur (Students' Journal of Accounting and Banking, 2017)
The study examines the effect of Sale and Purchase Financing, Profit Share Financing, Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR) and Operational Expense Operating Income (BOPO) on Return On Assets (ROA). The population this research is Islamic Comercial Bank Listed in Bank Indonesia are supervised OJK in 2012 – 2016. The sampling method used purposive sampling with the observation period from 2012 to 2016. Relationship and (or) influence between variable is described by using multiple regression analysis. The results of this study indicate that the Sale and Purchase Financing and Capital Adequacy Ratio (CAR) has no effect on Return On Assets (ROA). Whereas Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) and Operating Expense Operating Income (BOPO) has negative effect on Return On Assets (ROA).Keywords: Return On Assets (ROA), Sale and Purchase Financing, Profit Share Financing, Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Operational Expense Operating Income (BOPO)